Effects of neuromuscular electrical stimulation and voluntary commands on the spinal reflex excitability of remote limb muscles - Kato, Tatsuya; Sasaki, Atsushi; Yokoyama, Hikaru; Milosevic, Matija; Nakazawa, Kimitaka (Experimental Brain Research, 2019)
It is well known that contracting the upper limbs can affect spinal reflexes of the lower limb muscle, via intraneuronal networks within the central nervous system. However, it remains unknown whether neuromuscular electrical stimulation (NMES), which can generate muscle contractions without central commands from the cortex, can also play a role in such inter-limb facilitation. Therefore, the objective of this study was to compare the effects of unilateral upper limb contractions using NMES and voluntary unilateral upper limb contractions on the inter-limb spinal reflex facilitation in the lower limb muscles. Spinal reflex excitability was assessed using transcutaneous spinal cord stimulation (tSCS) to elicit responses bilaterally in multiple lower limb muscles, including ankle and thigh muscles. Five interventions were applied on the right wrist flexors for 70 s: (1) sensory-level NMES; (2) motor-level NMES; (3) voluntary contraction; (4) voluntary contraction and sensory-level NMES; (5) voluntary contraction and motor-level NMES. Results showed that spinal reflex excitability of ankle muscles was facilitated bilaterally during voluntary contraction of the upper limb unilaterally and that voluntary contraction with motor-level NMES had similar effects as just contracting voluntarily. Meanwhile, motor-level NMES facilitated contralateral thigh muscles, and sensory-level NMES had no effect. Overall, our results suggest that inter-limb facilitation effect of spinal reflex excitability in lower limb muscles depends, to a larger extent, on the presence of the central commands from the cortex during voluntary contractions. However, peripheral input generated by muscle contractions using NMES might have effects on the spinal reflex excitability of inter-limb muscles via spinal intraneuronal networks.